2022
DOI: 10.1111/geb.13514
|View full text |Cite
|
Sign up to set email alerts
|

Warmer and drier conditions have increased the potential for large and severe fire seasons across south‐eastern Australia

Abstract: Aim:The aims were: (1) to identify the environmental drivers of interannual variation in wildfire extent and severity; (2) to examine temporal trends in climatic potential for large and severe wildfires; and (3) to assess whether environmental conditions experienced during the 2019-2020 mega-fire season were anomalous.Location: South-eastern Australia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(32 citation statements)
references
References 82 publications
2
28
0
2
Order By: Relevance
“…Pascolini‐Campbell et al (2022) identified the importance of terrain in driving fire severity in Southern California, with higher fire severity observed at high elevations and on steep slopes. In both south‐eastern Australia and the Western United States, the large burn areas of 2020 were largely consistent with long‐term trends of increasing fire size and warming and drying (Collins et al, 2022; Safford et al, 2022).…”
Section: What Is Driving Extreme Fire Seasons?supporting
confidence: 63%
See 2 more Smart Citations
“…Pascolini‐Campbell et al (2022) identified the importance of terrain in driving fire severity in Southern California, with higher fire severity observed at high elevations and on steep slopes. In both south‐eastern Australia and the Western United States, the large burn areas of 2020 were largely consistent with long‐term trends of increasing fire size and warming and drying (Collins et al, 2022; Safford et al, 2022).…”
Section: What Is Driving Extreme Fire Seasons?supporting
confidence: 63%
“…In the Australian Black Summer, Brazilian Pantanal and western US fires, the large burn areas were found to be a function of extremely dry conditions (Collins et al, 2022;Coop et al, 2022;Ferreira Barbosa et al, 2022;Pascolini-Campbell et al, 2022;Safford et al, 2022).…”
Section: Changing Fire Regimesmentioning
confidence: 99%
See 1 more Smart Citation
“…Annual area burned, the area burned by high severity fire and the size of high severity patches have increased across the eucalypt forest biome of south-eastern Australia over the past three decades, in response to worsening drought and fire weather (Tran et al 2020;Collins et al 2022). Very large wildfires (>100 000 ha) with large contiguous patches of high severity fire (>5000 ha) are becoming a more frequent component of fire regimes across this biome (Collins et al 2021a).…”
Section: Discussionmentioning
confidence: 99%
“…Large mixed-severity wildfires are common across the forests of south-eastern Australia (Collins et al 2021a), generally occurring in summer during periods of drought (Collins et al 2022). Prescribed burning is commonly applied in autumn for fuel hazard reduction, resulting in a fire regime consisting of both management burns and wildfires, with inter-fire intervals ranging from ~5 to >100 years (Murphy et al 2013).…”
Section: Study Areamentioning
confidence: 99%